Twenty‐first century bioarchaeology: Taking stock and moving forward. (22nd March 2022) - Buikstra, Jane E.; DeWitte, Sharon N.; Agarwal, Sabrina C.; Baker, Brenda J.; Bartelink, Eric J.; Berger, Elizabeth; Blevins, Kelly E.; Bolhofner, Katelyn; Boutin, Alexis T.; Brickley, Megan B.; Buzon, Michele R.; de la Cova, Carlina; et al.
Abstract: This article presents outcomes from a Workshop entitled "Bioarchaeology: Taking Stock and Moving Forward, " which was held at Arizona State University (ASU) on March 6–8, 2020. Funded by the National Science Foundation (NSF), the School of Human Evolution and Social Change (ASU), and the Center for Bioarchaeological Research (CBR, ASU), the Workshop's overall goal was to explore reasons why research proposals submitted by bioarchaeologists, both graduate students and established scholars, fared disproportionately poorly within recent NSF Anthropology Program competitions and to offer advice for increasing success. Therefore, this Workshop comprised 43 international scholars and four advanced graduate students with a history of successful grant acquisition, primarily from the United States. Ultimately, we focused on two related aims: (1) best practices for improving research designs and training and (2) evaluating topics of contemporary significance that reverberate through history and beyond as promising trajectories for bioarchaeological research. Among the former were contextual grounding, research question/hypothesis generation, statistical procedures appropriate for small samples and mixed qualitative/quantitative data, the salience of Bayesian methods, and training program content. Topical foci included ethics, social inequality, identity (including intersectionality), climate change, migration, violence, epidemic disease, adaptability/plasticity, the osteological paradox, and the developmental origins of health and disease. Given the profound changes required globally to address decolonization in the 21st century, this concern also entered many formal and informal discussions.